Foundry production optimization with PolygonSoft computer simulation system - S. V. Korenyugin; M. A. Sadokha; A. A. Franchuk; S. D. Shatillo; M. A. Ripinsky (Литьë и металлургия, 2025)
The article presents an analysis of the application of the casting process modeling system (CPMS) “PolygonSoft” for the optimization of technological processes in casting production. The study examines the visualization of pouring and liquid phase distribution, as well as the analysis of temperature fields and stresses. Special attention is given to the assessment of alloy crystallization, monitoring of the liquid phase percentage, and prediction of the probability of shrinkage defect formation.